Synthesis, antifungal and anti-hiv activities of new heterocyclic compounds - Al-Maqtari, Helmi Mohammed AbdulGhani (2019)
Thiophene chalcones, pyrazolines and 1,5-benzodiazepines are important heterocyclic compounds which show broad spectrum of biological activities. Three series of heterocyclic chalcones and their N-acetylated pyrazoline derivatives have been synthesized in low to good yields. The first step in this study is the synthesis of 3-acetyl-2,5-dichlorothiophene and 2-acetyl-5-chlorothiophene as heterocyclic ketones using Friedel-Crafts acylation. All thiophene chalcones were synthesized in three separate reactions by Claisen-Schmidt reaction of substituted thiophene aldehydes with ketones. Several acetophenone derivatives (series 2 and 3) were produced by cyclization reaction using hydrazine hydrate to form new and known N-acetylated pyrazoline derivatives. A series of substituted 1,5-benzodiazepines were synthesized in moderate to good yields. 4-Methyl-1,3,4,5-tetrahydro-2H-1,5-benzodiazepin-2-one was synthesized as starting material by reacting ortho phenylenediamine and crotonic acid in the presence of toluene. Cyclization of the starting material with appropriate acid chlorides, unsubstituted and five types of groups (fluoro, chloro, bromo, methyl and methoxy) attached at ortho, para and meta position of phenyl ring in the presence of triethylamine and anhydrous tetrahydrofuran have furnished substituted 1,5-benzodiazepines. The structures of the compounds were confirmed by infrared (IR), 1H NMR and 13C NMR (1D and 2D) nuclear magnetic resonance spectroscopies. Compounds of series 2 and 3 were tested for their antifungal activities against two types of pathogenic strains, namely Candida albicansa and Aspergillus niger with fluconazole as standard drug. The results for series 2 showed that the presence of bromo and methoxy substitution at para position on phenyl ring in chalcone and pyrazoline, respectively, resulted in significant enhancement in potency against both tested fungal strains with MIC value of ＞64 µg/mL. Compound carrying para fluoro on phenyl ring in pyrazoline derivatives exhibited the highest potency with MIC value of ＞32 µg/mL and 64 µg/mL against C. albicans and A.niger, respectively, among the series 3. The anti-HIV-1 RT assay of substituted 1,5-benzodiazepines (series 4) showed that the presence of chloro substitution at meta and ortho position inhibited the activity of HIV-1 RT with IC50 values 6.87 and 8.62 µM, respectively.